2010
DOI: 10.1080/01411591003656757
|View full text |Cite
|
Sign up to set email alerts
|

Martensitic transformation and physical properties of ‘steel–TiNi’ bimetal composite, produced by explosion welding

Abstract: The aim of this work is an investigation of structure and martensitic transformation in bimetal composite 'TiNi-stainless steel' produced by explosion welding. The results have shown that the mixture of chemical elements is observed in very narrow intervals of 6 mm close to the joint -2 mm from the TiNi side and 4 mm from the steel one. Micro-hardness distribution in the vicinity of the joint is non-monotonic in the interval of 60 mm. Connection of stainless steel and TiNi plates by explosion welding leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…In [47,48] it was shown that the plastic deformation induced during welding lead to a partial depression of the martensitic transformation, but with a post-weld heat treatment, the kinetics of this transformation could be recovered. No brittle intermetallics between NiTi and stainless steel were found after explosive welding.…”
Section: Explosive Weldingmentioning
confidence: 99%
See 1 more Smart Citation
“…In [47,48] it was shown that the plastic deformation induced during welding lead to a partial depression of the martensitic transformation, but with a post-weld heat treatment, the kinetics of this transformation could be recovered. No brittle intermetallics between NiTi and stainless steel were found after explosive welding.…”
Section: Explosive Weldingmentioning
confidence: 99%
“…More recently, and after the preliminary work of Prummer et al [46], Belyaev et al [47][48][49] produced NiTi/stainless steel composites by explosive welding. In [47,48] it was shown that the plastic deformation induced during welding lead to a partial depression of the martensitic transformation, but with a post-weld heat treatment, the kinetics of this transformation could be recovered.…”
Section: Explosive Weldingmentioning
confidence: 99%
“…As for the researches on FG-SMA materials, the studies are mainly focused on the following situations: (1) graded SMA composites with different component fractions, such as gradient composites of NiTi alloy that with different fractions of NiTi and the other elastic material (Belyaev et al, 2010; Fu et al, 2003; Lester et al, 2011; Liu et al, 2013; Tian et al, 2009; Xue et al, 2013; Zheng et al, 2007a), two-phase materials with different gradient fractions of Ni and Ti (Belyaev et al, 2014; Lim et al, 2014; Martins et al, 2010; Yan et al, 2007), and the functionally graded porous SMA material with gradient variation porosity (Zhang et al, 2007). (2) FG-SMA material with the gradient transformation stress and the gradient transformation strain created through the different heat treatment processes or the adjustment of microstructure or geometric size of SMA material (Meng et al, 2012; Shariat et al, 2012, 2013a, 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…The above reports on the FG-SMA materials are mainly focused on the material preparation, experimental testing, and experimental characterization (Belyaev et al, 2010(Belyaev et al, , 2014Lim et al, 2014;Martins et al, 2010;Meng et al, 2012;Razali and Mahmud, 2015;Tian et al, 2009;Yan et al, 2007;Zhang et al, 2007;Zheng et al, 2007a). However, the research on how to describe the mechanism of phase transformation and microstructure evolution is still in the initial exploring stage (Liu et al, 2013;Shariat et al, 2012Shariat et al, , 2013aShariat et al, , 2013b.…”
Section: Introductionmentioning
confidence: 99%
“…The composite, which contains a shape-memory alloy, demonstrates a nonlinear 'displacement-temperature' dependence, due to a sharp change in the strain of the shape-memory alloy layer during cooling and heating as a result of the temperature range during a Martensitic transformation [2]. The value of the strain variation depends on the sequence of the Martensitic transformations occurring in the shape-memory alloy layer, the value of the residual strain, and the ratio of the thickness of the shape-memory alloy layer to the total thickness of the sample [3][4].…”
Section: Introductionmentioning
confidence: 99%